2013
DOI: 10.1111/aas.12160
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil as analgesia for labour pain

Abstract: Background To collect updated information about pharmacological labour analgesia in Norway, especially systemic opioids and epidural. Evaluation of efficacy and safety with remifentanil intravenous patient‐controlled analgesia (IVPCA) for pain relief during labour. To compare remifentanil IVPCA with epidural analgesia (EDA) regarding efficacy and safety during labour. Methods In paper I, two national surveys identified Norwegian labour analgesia methods and changes during the study period (2005–2008). Paper II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 126 publications
(390 reference statements)
0
1
0
Order By: Relevance
“…Tveit reported that patient-controlled IV remifentanil might be an alterna- tive to epidural analgesia owing to adequate labour analgesia, high maternal satisfaction and non-serious adverse effects. Contrarily, it was emphasized that remifentanil causes sedation and oxygen desaturation in mothers; therefore, cases should be closely monitored by experienced personnel during administration, and remifentanil needs to be preferred instead of morphine or meperidine for labour analgesia in the event epidural analgesia is not applicable (15).…”
Section: Discussionmentioning
confidence: 99%
“…Tveit reported that patient-controlled IV remifentanil might be an alterna- tive to epidural analgesia owing to adequate labour analgesia, high maternal satisfaction and non-serious adverse effects. Contrarily, it was emphasized that remifentanil causes sedation and oxygen desaturation in mothers; therefore, cases should be closely monitored by experienced personnel during administration, and remifentanil needs to be preferred instead of morphine or meperidine for labour analgesia in the event epidural analgesia is not applicable (15).…”
Section: Discussionmentioning
confidence: 99%